The Criminal Sanctions In The Object Transfer Crime On Fiduciary Guarantee By Debtor - Drajat Prasetiyawan; Sri Kusriyah (Law Development Journal, 2021)
This study aims to determine and examine the criminal sanctions in the criminal act of transferring the object of fiduciary security by the debtor. This study uses a normative juridical approach, which is descriptive analysis. The data used is secondary data obtained through literature study, which is then analyzed qualitatively. The results of this study are that criminal sanctions in the criminal act of transferring the object of fiduciary security by debtors are regulated in Article 36 of Act No. 42 of 1999. Article 36 of Act No. 42 of 1999 has similarities with Article 372 of the Criminal Code regarding embezzlement. The provisions of Article 36 of Act No. 42 of 1999 contain a penalty of 2 (two) years and a maximum fine of IDR 50,000,000 (fifty million rupiah).